2021
DOI: 10.3389/fenrg.2021.618368
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3 Thin Films on Magnesium: Assessing the Impact of an Artificial Solid Electrolyte Interphase

Abstract: Among the many emerging technologies under investigation as alternatives to the successful Lithium-ion battery, the magnesium battery is promising due to the wide availability of magnesium, its high volumetric capacity, and the possibility for safety improvements. One of the largest challenges facing rechargeable magnesium batteries is the formation of a passivation layer at the Mg metal anode interface when reactive species in the electrolyte are reduced at the electrode-electrolyte interface. To control the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…[18] The XPS spectra of Mg 2p at 51.5 eV can be fit into the MgCO 3 part in MgCO 3 •3 H 2 O (Figure S11a). [19] These peaks decrease significantly after the charge process, indicating the disappearance of MgCO 3 •3 H 2 O. As shown in Figure 3c, there is a sharp peak at 1120 cm À 1 and a broad peak at about 3500 cm À 1 , which S2).…”
Section: Angewandte Chemiementioning
confidence: 80%
See 2 more Smart Citations
“…[18] The XPS spectra of Mg 2p at 51.5 eV can be fit into the MgCO 3 part in MgCO 3 •3 H 2 O (Figure S11a). [19] These peaks decrease significantly after the charge process, indicating the disappearance of MgCO 3 •3 H 2 O. As shown in Figure 3c, there is a sharp peak at 1120 cm À 1 and a broad peak at about 3500 cm À 1 , which S2).…”
Section: Angewandte Chemiementioning
confidence: 80%
“…In O 1s spectra, the C−O bond at 532.6 eV as well as O−H band at 533.6 eV belongs to MgCO 3 ⋅3 H 2 O (Figure 3b) [18] . The XPS spectra of Mg 2p at 51.5 eV can be fit into the MgCO 3 part in MgCO 3 ⋅3 H 2 O (Figure S11a) [19] . These peaks decrease significantly after the charge process, indicating the disappearance of MgCO 3 ⋅3 H 2 O.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…The XPS results of the discharged products in MCB‐dry is obtained with a CO 3 2− peak at 290 eV in C 1s spectra (Figure 4a) and the appearance of a C−O band at 532.6 eV in O 1s spectra (Figure 4b), which associates with MgCO 3 [17, 18] . Peaks at 51.5 eV in Mg 2p spectra are also remarkable at the discharged state (Figure S11b) [19] . All the signals barely change after the charge process, which means the discharge product is difficult to decompose.…”
Section: Figurementioning
confidence: 95%
“…While much effort in the field of Mg batteries to battle these issues has been made to synthesize more complex Mg salts and create electrolytes that do not passivate the surface or reduce passivation, , in the last several years, even though still few in number, more studies have shown that Mg metal anodes can be successfully protected with artificial SEI (ASEI) layers or shed light on the prospective approaches that can greatly mitigate the passivation of the Mg surface but still allow the transport of Mg 2+ ions. A few approaches to the formation of an ASEI have been investigated, such as utilizing electrolyte additives and preforming layers using controlled chemical reactions. For example, Li et al formed an MgI 2 protective layer by adding I 2 to the electrolyte .…”
Section: Introductionmentioning
confidence: 99%